Gonadoblastoma-associated mixed germ cell tumour in 46,XY complete gonadal dysgenesis (Swyer syndrome): Analysis of Y chromosomal genotype and OCT3/4 and TSPY expression profile - Ng, S.B. (2012)
10.1111/j.1365-2559.2008.02988.x